Securing the Truth: Scientific Principles and Practices in Crime Scene Management - Trisha Kamble (AG Volumes, 2026)
Crime scene management is the scientific basis of criminal investigation where the truth is determined by systematically gathering, documenting, preserving, analysing, and interpreting evidence. The integrity of the crime scene procedures and adherence to scientifically proven principles are crucial to the reliability of forensic findings and judicial outcomes. This review focuses on the concept and goals of crime scene management and highlights the scientific principles involved with forensics, such as Locard's Exchange Principle, individuality, progressive change, scientific analysis and objectivity. It also addresses the standardized procedures used in the evaluation of a crime scene, evidence identification, evidence collection and preservation, chain of custody, crime scene laboratory examination, and reconstructing criminal events. The review also examines how forensic evidence analysis is used to reconstruct a criminal incident and the potential of new technologies like 3D documentation, artificial intelligence, drones, digital forensics and geospatial systems in contemporary investigations. This review highlights the scientific soundness of crime scene management, which enhances the accuracy of investigations, maintains evidence integrity, and contributes to the fair and just administration of justice by combining theory with methodology and technology. Implementing these scientific practices is still critical to the truth and to increasing confidence in forensic science and criminal justice systems.